'Anglicanism in a Bottle?' Theological Implications of Sexualities Education for Anglican Ordinands. Issue 4 (2nd October 2017) - Nixon, David; Cornwall, Susannah
Abstract : This article develops the initial findings of the small-scale research project Mind the Gap to ask what theological insights might be drawn from this enquiry into contemporary theological education for ordinands concerning sexualities. Three areas are suggested: the relationship between theology and other disciplines in the interrogation of human behaviour (including the theological understanding of lived experience); a further investigation of identity, authority and power; a response to the concept of 'theological capital' in terms of sexualities. The authors conclude that embodied theologies of desire may connect more healthily the abstract and the (sexually) concrete, as well as renewing tired secular concepts with new Christian insights. Ordinands are encouraged to engage cognitively at a meta-level in analysing and appreciating differences, of which they are already aware from their pastoral practice.